Quantification of sugar intake and mineralization of teeth in 13-15-year-old subjects - A pilot study - Therathil, Sona; V. Kakarla, Prasad (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2022)
Background: Dental caries begins with the initiation of demineralization which is a reversible process. Diet, especially intake of sugar, is an important aetiological factor for demineralization of enamel which eventually leads to caries. Aim: This study aims to understand the quantitative relationship between sugar consumption and mineralization by finding out the change in mineralization of teeth as a result of the change in the sugar score. Settings and Design: This interventional study was done among 119 teeth of 19 subjects who were between the ages of 13-15 years in Hubli city. Materials and Methods: Sugar score was calculated from a 5-day diet history of the subjects and a DIAGNOdent pen was used to indicate the mineralization value of the teeth before the intervention. Diet counseling was given as an intervention after which sugar score and DIAGNOdent scores were measured again after 14 days and compared with the baseline values. Statistical Analysis: Descriptive statistics and a linear regression analysis was done to determine the relationship between the variables. Results: Sugar score and DIAGNOdent score after 14 days were found to have reduced significantly by 41.6% and 20.3% respectively from the baseline values. The Linear Regression indicated that a reduction of sugar score by 5 resulted in a decrease of DIAGNOdent score by 0.16. Conclusion: The findings of the present study suggest that the modification of sugar consumption brought about a significant improvement in the mineralization of the demineralized teeth thus making diet counseling an effective preventive strategy for caries prevention.